Review of potential simultaneous operations for the surgical rehabilitation of patients with thyroid eye disease - D.S. Atarshchikov; E.Yu. Korchemkina (РМЖ "Клиническая офтальмология")
D.S. Atarshchikov1, E.Yu. Korchemkina2 1Central Clinical Hospital and Polyclinic of the Department for Presidential Affairs, Moscow, Russian Federation 2Academy of Postgraduate Education of the Federal Scientific and Clinical Center of the Federal Medical Biological Agency of Russian Federation, Moscow, Russian Federation The importance of revising the traditional multi-stage approach to the surgical rehabilitation of patients with thyroid eye disease is supported by multiple reasons, such as high operation costs, anesthesia-related increase in a burden for patients, and repeated surgical incisions associated with a delayed healing of surgical wounds. Over the past two decades, the orbital surgeons have attempted to solve the problem by combining several operations into a single-stage procedure. The article reviews the results of studies elucidating various simultaneous surgical techniques for orbital decompression, because the surgical treatment of exophthalmos is a "cornerstone" in solving functional problems arising from Graves’ orbitopathy. Moreover, the optimal planning depends on the severity of aesthetic problems in the periorbital region and the associated changes of eyelids and midface. Thus, it is necessary to consider multiple potential solutions within a single anesthesia exposure, the availability of surgeons with the appropriate skills or the involvement of a multidisciplinary team. In conclusion, the authors, referring to their own experience and the latest articles in international editions, propose anatomical and physiological criteria for selecting candidates for simultaneous orbit decompression surgery and for predicting surgical treatment outcomes in such patients. Keywords: orbital decompression, eyelid retraction, simultaneous operations, restrictive strabismus, thyroid eye disease, canthoplasty, exophthalmos. For citation: Atarshchikov D.S., Korchemkina E.Yu. Review of potential simultaneous operations for the surgical rehabilitation of patients with thyroid eye disease. Russian Journal of Clinical Ophthalmology. 2022;22(3):187–190 (in Russ.). DOI: 10.32364/2311-7729-2022-22-3-187-190.